2014
DOI: 10.21098/bemp.v17i1.52
|View full text |Cite
|
Sign up to set email alerts
|

Konvergensi Penerimaan Dan Pengeluaran Pemerintah Provinsi Di Indonesia: Pendekatan Data Panel Dinamis Spasial

Abstract: The study analyse sigma and beta convergence of provincial government revenues and expenditures in Indonesia (APBD) by using panel data 30 provinces over the period 2000-2012. The variables used in this study consists of real income per capita and the revenues and expenditures variables in the APBD. The study also included a spatial weights matrix to analyse dependency among provinces. Spatial weights matrix used consists of two types of weights, the real income per capita and the geographical distance. Testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 0 publications
2
15
0
3
Order By: Relevance
“…It declined from 0.849 in 2005 to 0.836 in 2014. A study from Dekiawan (2014) [3] agreed that all variables of local revenue bears a tendency to be more even, as represented by the decrease of CV year after year.…”
Section: Discussionmentioning
confidence: 98%
“…It declined from 0.849 in 2005 to 0.836 in 2014. A study from Dekiawan (2014) [3] agreed that all variables of local revenue bears a tendency to be more even, as represented by the decrease of CV year after year.…”
Section: Discussionmentioning
confidence: 98%
“…Pendekatan yang diperlukan untuk memprediksi terjadinya kesetaraan pertumbuhan ekonomi antar daerah di Provinsi Bali adalah pendekatan konvergensi. Konvergensi ini digunakan untuk melihat kapan kesetaraan ekonomi antar daerah atau negara itu terjadi (Schmitt & Starke, 2011;Dekiawan, 2014). Konvergensi juga dijelaskan sebagai kondisi dimana terjadinya kemiripan ekonomi antar daerah (Barro & Sala-I-Martin, 1992;Dana, 2018).…”
Section: Pendahuluanunclassified
“…Blundell & Bond (1995) showed that the GMM of the system has better finite sample properties in the case of short panels with presistent series (autoregressive terms of about 0.8 and 0.9). This research model is also the same as the one used (Dekiawan, 2014), where the model is estimated using the smallest squared panel, fixed effect, random effect, as well as the first difference between GMM (GMM-DIFF) and GMM system (GMM-SYS). The amount of government spending is equal to the growth rate (Dekiawan, 2014), which is recorded in the trade balance (DTBAL) (Firdaus, 2018).…”
Section: A Data Types and Sourcesmentioning
confidence: 99%
“…This research model is also the same as the one used (Dekiawan, 2014), where the model is estimated using the smallest squared panel, fixed effect, random effect, as well as the first difference between GMM (GMM-DIFF) and GMM system (GMM-SYS). The amount of government spending is equal to the growth rate (Dekiawan, 2014), which is recorded in the trade balance (DTBAL) (Firdaus, 2018).…”
Section: A Data Types and Sourcesmentioning
confidence: 99%